The Significant Changes in the New Polish Translation of the Code of Canon Law - Majer, Piotr (Prawo Kanoniczne, 2022)
This article offers a discussion about the revised translation of the 1983 Code of Canon Law. The new translation was approved by the Polish Bishops’ Conference on March 14, 2022. The author discusses the most important changes in the translation into Polish all of books of the Code, giving the justification for the revision. In most cases, the changes consist of linguistic corrections, especially stylistic ones. Sometimes, however, thorough verification of the existing translation revealed the necessity of more substantial modifications. One of the reasons inspiring the new translation was the ambition to adjust the language of the Code of Canon Law to the Polish language of the law and lawyers’ language.